Gender Gap in German Management Positions and Recommendations for Equality - Bekdemir, Ilham; Ackermann, Margarita; Beil, Larissa; Cröger Nils; Mujtaba, Bahaudin G. (Advances in Social Sciences Research Journal, 2015)
Abstract Companies depend on highly qualified executives to survive and to keep up with the increasing global competition. Modern and globally dynamic companies often get criticized for the underrepresentation of women in management and senior level executive positions. These globally dynamic understand that they cannot do without the capability and commitment of qualified women to be successful in the future. Furthermore it has been proven that mixed teams of women and men work more efficiently, their capability grows faster, and they earn higher profits in comparison to homogeneous teams. Nevertheless, in many companies gender discrimination is a daily life. The result of this is an unequal allocation of gender gap in management positions favouring men. This article explores some of the reasons for the gender gap problem and how it can be solved. The authors provide suggestions to solve the dilemma and to overcome certain circumstances of mentality patterns in the organization’s culture. Key Words: Gender, discrimination, glass ceiling, stereotypes, Germany, Norway.